International Maritime Conventions - Berlingieri, Francesco (Lloyd's shipping law library, 2013)
For the first time, this unique text brings together all private international maritime law conventions alongside expert commentary and analysis. Truly global in approach, the book covers each of the nineteen conventions currently in force, all scrutinised by this internationally-acclaimed author. It also examines important maritime conventions not yet in force, including the topical Rotterdam Rules. Split into three convenient volumes, this comprehensive resource provides a thorough treatment of both wet and dry shipping treaties, combining breadth of coverage with depth of analysis